Effect of Cerium Oxide Nanoparticles as an Additive in Cryopreservation of Gir Bull Spermatozoa - Z Solanki, Jayesh; B Vala, Karshan; R Ram, Dilip; B Odedara, Arjun; K Chaudhary, Jignesh; J Devmurari, Yash (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The present investigation was carried out on semen of four Gir bulls at Cattle Breeding Farm, Junagadh for a period of 6 months (Feb July 2024). Semen (n=16 ejaculates) was collected using artificial vagina (Danish model) once weekly from each bull. The semen was evaluated for sperm quality attributes along with oxidative stress parameters at post-thaw stage of cryopreservation using different concentrations of Cerium Oxide Nanoparticles, viz., 25 µg/mL, 50 µg/mL, 75 µg/mL CeO2NPs and a control AndroMed® extender. AndroMed® extender with 75 µg/mL CeO2NPs concentration had significantly (p<0.001) higher sperm motility, viability, HOST reactive sperm, acrosome integrity with lower sperm abnormality as compared to that of the 25 µg/mL and 50 µg/mL CeO2NPs and control extender. Mean malondialdehyde (MDA) levels in seminal plasma of post-thaw semen varied significantly between treated and control groups, but the value with 75 µg/mL CeO2NPs concentration was the lowest and it increased with the decreased level of CeO2NPs, and was highest in control group, while total antioxidants activity (TAC) increased proportionately with the increase in CeO2NPs concentration, suggesting its beneficial role as an antioxidant molecule. All the above post-thaw seminal attributes were better in extender containing CeO2NPs at 75 µg/mL concentration. The findings suggested the cryoprotective and antioxidant effects of CeO2NPs on bull spermatozoa by lowering free radicals and its associated oxidative stress.